ABCs of z/OS system programming Volume 6 - Rogers, Paul (IBM Corp., International Technical Support Organization, 2008)
The ABCs of IBM® z/OS® System Programming is an 11-volume collection that provides an introduction to the z/OS operating system and the hardware architecture. Whether you are a beginner or an experienced system programmer, the ABCs collection provides the information that you need to start your research into z/OS and related subjects. If you want to become more familiar with z/OS in your current environment or if you are evaluating platforms to consolidate your e-business applications, the ABCs collection can serve as a powerful technical tool. Following are the contents of the volumes: Volume 1: Introduction to z/OS and storage concepts, TSO/E, ISPF, JCL, SDSF, and z/OS delivery and installation Volume 2: z/OS implementation and daily maintenance, defining subsystems, JES2 and JES3, LPA, LNKLST, authorized libraries, IBM Language Environment®, and SMP/E Volume 3: Introduction to DFSMS, data set basics, storage management hardware and software, VSAM, System-managed storage, catalogs, and DFSMStvs Volume 4: Communication Server, TCP/IP, and IBM VTAM® Volume 5: Base and IBM Parallel Sysplex®, System Logger, Resource Recovery Services (RRS), global resource serialization (GRS), z/OS system operations, automatic restart management (ARM), and IBM Geographically Dispersed Parallel Sysplex"!(IBM GDPS®) Volume 6: Introduction to security, IBM RACF®, digital certificates and public key infrastructure (PKI), Kerberos, cryptography and IBM z9® integrated cryptography, Lightweight Directory Access Protocol (LDAP), and Enterprise Identity Mapping (EIM) Volume 7: Printing in a z/OS environment, Infoprint Server, and Infoprint Central Volume 8: An introduction to z/OS problem diagnosis Volume 9: z/OS UNIX System Services Volume 10: Introduction to IBM z/Architecture®, IBM System z® processor design, System z connectivity, logical partition (LPAR) concepts, hardware configuration definition (HCD), and Hardware Management Console (HMC) Volume 11: Capacity planning, performance management, Workload Manager (WLM), IBM Resource Measurement Facility"!(RMF"!, and System Management Facilities (SMF)
Online resource; title from cover (Safari, viewed August 27, 2014)
Keywords: z/OS; Operating systems (Computers); Z/OS; Systèmes d'exploitation (Ordinateurs); operating systems